Demographic characteristics of older immigrats – Poland - Kałuża-Kopias, Dorota (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Seniors on the one hand population clearly different from the younger-provoking reasons for change of residence - are much smaller economic factor (labor market), family (concluding marriage), there is no influence of the educational factor. The last quarter century is a period in which the Polish literature of geographical, demographic and gerontological research omits this topic. The purpose of this paper is to present selected determinants of older migrants to the Polish, as well as their spatial distribution in the provincial system in the past decade.